2020
DOI: 10.26650/eor.20200059
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetically driven immediate implant placement at lower molar area; an anatomical study

Abstract: PurposeTo examine the effectiveness and safety of immediate implant placement (IIP), we evaluated the risk of lingual plate perforation (LPP) and mandibular canal perforation (MCP) associated with posterior mandible anatomy using cone beam computed tomography (CBCT) images. Materials and MethodsA morphological study of the molar sockets of 135 patients (age: 18-84 y) was done and its relationship to the mandibular canal was investigated. The risk of LPP and MCP was recorded as yes or no. Mandibular cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Previous studies have predicted a higher risk of lingual perforation in U type mandible [ 7 ]. In this study, a tendency to be classified as U type in more posterior regions was found, which is similar to the results obtained in former studies [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have predicted a higher risk of lingual perforation in U type mandible [ 7 ]. In this study, a tendency to be classified as U type in more posterior regions was found, which is similar to the results obtained in former studies [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have predicted a higher risk of lingual perforation in U type mandible [ 7 ]. In this study, a tendency to be classified as U type in more posterior regions was found, which is similar to the results obtained in former studies [ 7 ]. Based on the data of the distance between the lingual outer plate surface and the implant surface at the apex in the simulation in this study, the immediate implantation in the mandibular second molar region presents a higher risk of lingual perforation than the first molar region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be mentioned, however, that the majority of studies on immediate implant placement are related to the maxillary aesthetic region. Immediate implant placement in the posterior region is studied much less, probably because those patients are less demanding and due to the different anatomical features of the extraction socket compared to that of the single-rooted teeth in the anterior maxilla [10,11]. Nevertheless, two systematic reviews mention that high survival rates have also been reported for immediate implant placement in molar regions [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A more sensible approach might be to place a single wide diameter implant in the inter‐radicular bone and in the center of the multi‐rooted socket, to prevent the unwanted compromises of the aforementioned options . Based on cone beam CT images, the dimensions of molar sockets are suitable for the placement of wide diameter implants, but the maximal implant length will be limited to avoid perforation of the sinus floor and the inferior alveolar nerve …”
Section: Introductionmentioning
confidence: 99%